2021
DOI: 10.1155/2021/9927311
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Vagus Nerve Stimulation Outcomes in Epilepsy

Abstract: Epilepsy as a common neurological disease is mostly managed effectively with antiepileptic medications. One-third of patients do not respond to medical treatments requiring alternative therapies. Vagus nerve stimulation (VNS) has been used in the last decades for the treatment of medically resistant epilepsy. Despite the extensive use of VNS in these patients, factors associated with clinical outcomes of VNS remain to be elucidated. In this study, we evaluated factors affecting VNS outcomes in epileptic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
0
3
0
4
Order By: Relevance
“…Overall, studies have identified several factors that could be beneficial for VNS therapy. It seems to be particularly effective in patients that have a shorter duration of epilepsy before the VNS implantation, in patients that predominantly experience generalized seizures and in those patients with a low seizure frequency before the implantation [ 1 , 6 , 7 , 18 ]. However, the available evidence on factors associated with the improved outcome following VNS in the treatment of epilepsy is rather heterogeneous and has not yet addressed the synergistic effects of VNS and pharmacotherapy [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, studies have identified several factors that could be beneficial for VNS therapy. It seems to be particularly effective in patients that have a shorter duration of epilepsy before the VNS implantation, in patients that predominantly experience generalized seizures and in those patients with a low seizure frequency before the implantation [ 1 , 6 , 7 , 18 ]. However, the available evidence on factors associated with the improved outcome following VNS in the treatment of epilepsy is rather heterogeneous and has not yet addressed the synergistic effects of VNS and pharmacotherapy [ 1 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems to be particularly effective in patients that have a shorter duration of epilepsy before the VNS implantation, in patients that predominantly experience generalized seizures and in those patients with a low seizure frequency before the implantation [ 1 , 6 , 7 , 18 ]. However, the available evidence on factors associated with the improved outcome following VNS in the treatment of epilepsy is rather heterogeneous and has not yet addressed the synergistic effects of VNS and pharmacotherapy [ 1 , 5 ]. Interestingly, there is growing evidence on synergistic effects of VNS and ketogenic diet showing that the seizure frequency is reduced more during their combination as compared to when either one is used alone [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Factors Affecting Vagus Nerve Stimulation Outcomes in Epilepsy (Abassi et al, 2019) Revisão sistemática A obtenção de total liberdade de convulsões através da ENV é rara, a literatura atual indica que a taxa de não resposta varia entre 25 a 65%.…”
Section: Mecanismo De Ação Da Envunclassified
“…A obtenção de total liberdade de convulsões após a ENV é rara, tendo a taxa de não resposta variando entre 25 a 65% (Abassi et al, 2019), mas há um impacto positivo na qualidade de vida em 50% dos pacientes (Guery, 2021).…”
Section: Neuroplasticidade E Estimulação Dounclassified
“…It has proven beneficial for patients with drug-resistant epilepsy (DRE) [ 2 ] who are non-eligible or have failed epilepsy surgery. Recent findings show an encouraging increase in the responder rate, with the most significant seizure frequency reduction observed within the first one to two years after starting therapy [ 3 , 4 ]. The efficacy of VNS stimulation increases with time after implantation, and earlier exposure to VNS improves prognosis [ 5 ], which may result from VNS-induced neuroplastic changes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%